Master coach The Consequences Workplace of the Head Nurse's Adherence to Nursing Professional Educational Ethics and Knowledge of Moral Dilemmas at King Abdulaziz Hospital, Makkah, Saudi Arabia - Asma Barnawi (KHD-Production, 2023)
Conducting ethics deals with standards of moral judgment. Every day, professional nurses are required to make ethical decisions about patient care. They must have good adequate practice and knowledge of ethics to make ethical decisions. In addition, a head nurse's respect for the respected climate can affect job adherence by improving nurses' professional values and raising their awareness toward moral and ethical issues facing care practice through acceptance and correction of errors, which leads to improved quality of care by enforcing values of the profession and prevents negative consequences of errors hiding. The aim of this study was to examine the consequences of the head nurse's adherence to respect educational programs on nurses' professional ethics and knowledge of moral dilemmas. This study method used a Quasi-experimental research design. Setting: The study was conducted at King Abdul Aziz Hospital. The Subjects were all head nurses who worked in the inpatient and outpatient units, and all staff nurses worked in the same departments. Research Instrument of four tools were used in this study; respect knowledge questionnaire, workplace respect climate Self- Assessment scale, nursing professional value Scale, and moral and ethical issue knowledge questionnaire. The results showed total knowledge score and levels of perceived workplace respect among head nurses were low before the program implementation. After the program implementation, they had higher scores with statistically significant differences; also, the staff nurse professional value scores and moral and ethical issues awareness scores increased after implementing a respect education program for head nurses. In Conclusion, the respective training program positively affected head nurses by increasing their knowledge and self-assessment about perceived workplace respect after the program implementation. Recommendations were periodical conferences and programs for head nurses must develop respect skills, behaviors, and communication to motivate the worth of their professional values towards nursing and acknowledge moral and ethical knowledge.